The Neuroanatomical Basis of the 5-HT Syndrome and Harmalineinduced Tremor - Lalonde, Robert; Strazielle, Catherine (Current Reviews in Clinical and Experimental Pharmacology, 2024)
The 5-HT syndrome in rats is composed of head weaving, body shaking, forepaw treading, flat body posture, hindlimb abduction, and Straub tail. The importance of the brainstem and spinal cord for the syndrome is underlined by findings of 5,7-dihydroxytryptamine (5,7-DHT)-induced denervation supersensitivity in response to 5-HT-stimulant drugs. For head weaving and Straub tail, supersensitivity occurred when the neurotoxin was injected into the cisterna magna or spinal cord, for forepaw treading in cisterna magna, and for hindlimb abduction in the spinal cord. Although 5,7- DHT-related body shaking increased in the spinal cord, the sign decreased when injected into the striatum, indicating the modulatory influence of the basal ganglia. Further details on body shaking are provided by its reduced response to harmaline after 5-HT depletion caused by intraventricular 5,7-DHT, electrolytic lesions of the medial or dorsal raphe, and lesions of the inferior olive caused by systemic injection of 3-acetylpyridine along with those found in Agtpbp1pcd or nr cerebellar mouse mutants. Yet the influence of the climbing fiber pathway on other signs of the 5-HT syndrome remains to be determined.
Keywords: body shaking